Mechanisms Of Managing Human Capital In The Educational Process And Matching Conflict Situations (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
In this article, the field of pedagogy is the formation of a person according to the purpose, the orientation of existing capital and resources, and its essence is to show the social aspect and to teach and master, the compatibility of activities, this approach, the possibility of coordinating human capital without conflicts, education on the basis of a pedagogical innovative educational cluster the socio-pedagogical conditions of the development of talent and ability of the recipient, constructive implementation of relations on this issue and implementation into the life of the society are discussed.